2015
DOI: 10.1038/srep08830
|View full text |Cite
|
Sign up to set email alerts
|

Substitution-induced spin-splitted surface states in topological insulator (Bi1−xSbx)2Te3

Abstract: We present a study on surface states of topological insulator (Bi1−xSbx)2Te3 by imaging quasiparticle interference patterns (QPI) using low temperature scanning tunneling microscope. Besides the topological Dirac state, we observed another surface state with chiral spin texture within the conduction band range. The quasiparticle scattering in this state is selectively suppressed. Combined with first-principles calculations, we attribute this state to a spin-splitted band induced by the substitution of Bi with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
(38 reference statements)
2
14
0
1
Order By: Relevance
“…Hence, the location of μ associated with a peak gives a measure of Γ 0 . Estimating μ from the Hall data assuming a Fermi velocity of 3.9 × 10 5 m/s 34 , 35 (see Fig. 2d inset), we obtain for our sample meV, corresponding to a mean free path v F / Γ 0 of ~ 70 Å.…”
Section: Discussionmentioning
confidence: 91%
“…Hence, the location of μ associated with a peak gives a measure of Γ 0 . Estimating μ from the Hall data assuming a Fermi velocity of 3.9 × 10 5 m/s 34 , 35 (see Fig. 2d inset), we obtain for our sample meV, corresponding to a mean free path v F / Γ 0 of ~ 70 Å.…”
Section: Discussionmentioning
confidence: 91%
“…X. He et al [121] reported MBE grown (Bi x Sb 1−x ) 2 Te 3 on SrTiO 3 substrates. In their work, a sheet density as low as 3 × 10 12 cm −2 was obtained at around x = 0.5.…”
Section: Ternarymentioning
confidence: 99%
“…Investigation of the surface (0001) morphology with atomic resolution in the constant current mode Se atoms in the solid solutions [34,35] or the formation of structural defects [33]. [37], topological insulators Bi 1.5 Sb 0.5 Te 1.7 Se 1.3 [34] and (Bi 1-x Sb x ) 2 Te 3 [35]. Besides, more intense second-order spectral components were observed in the solid solution with an increase of Se content at x = 1.2 and y = 0.09 as compared with x = 1.6, y = 0.06 (figures 3b, 3d).…”
Section: Surface Morphologymentioning
confidence: 99%
“…The work is devoted to study of the surface states of Dirac fermions in p-type (Bi, Sb) 2 (Te, Se) 3 thermoelectrics with substitution of atoms in the Bi and Te sublattices by scanning tunneling microscopy (STM) and spectroscopy (STS). At present, STM/STS methods are used to obtain the local characteristics of the surface electronic states of Dirac fermions [17][18][19][20], along with angle-resolved photoelectron spectroscopy (ARPES) [17,[21][22][23] and transport properties [24][25][26]. STM/STS permit to determine the peculiarities of morphology and tunneling differential conductance that define the topological surface states, namely the Dirac point energy E D , the top of the valence band E V , the bottom of the conduction band E C , the energy gap E g , and the surface concentration of Dirac fermions n s in dependence on the of solid solution composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation